WORKSHOP PEMANFAATAN GOOGLE CLASSROOM SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN DIGITAL MASA PANDEMI COVID-19 - Sarma Panggabean; Pontas Jamaluddin Sitorus (Bajang Institute, 2021)
Google classroom is a mixed learning platform that is used in every educational setting to find solutions to the difficulties of creating, sharing and classifying paperless assignments. In the context of classroom learning, educators in the digital era must be able to utilize digital means as a medium in teaching. This community service aims to provide training on the use of Google classroom to 30 teachers at UPT SDN 064023 Medan Tuntungan as a digital learning medium during the Covid-19 pandemic. The method used is the dialogical discussion method. This method is carried out by delivering material by the resource person. The delivery of the material is interspersed with question and answer discussions between the teacher and the resource person. Then a simulation is carried out regarding the use of Google Classroom features for the learning process. The result of this workshop is that every teacher can use google classroom in the learning process at UPT SDN 064023 Medan Tuntungan so that students can still get good learning despite the current Covid-19 pandemic.